Desenvolvimento de Nanossistemas contendo Tambjaminas: Caracterização Físico-Química e Validação In Vitro em Linhagem de Câncer Colorretal (Hct-116). - Oliveira, Fátima de Cassia Evangelista de (2017)
Cancer has progressively becomes a major public health problem, is responsible for one in every six deaths in the world. Malignant tumors affecting the colon and rectum are ranked third in cancer incidence and are the fourth cause of cancer-related global mortality. Tambjamines are alkaloids whose main natural function is the chemical defense of their organisms against predators, studies have shown witch these substance exhibits a broad class of biological activity, including antitumor properties, but with high toxicity. In this context, nanotechnology provides the creation of nano-drugs, at nanoscale (10-9), that present differents physico-chemicals properties and that can be used in the diagnosis, prevention, therapy or products directed to health, including the cancer. Thus, the aim of the present study was to encapsulate and characterize two nanosystems, containing Tambjamines (I and J) and to evaluate their antiproliferative effects in vitro on tumor and non-tumor cell lines. For this, the encapsulation systems were tested for PLGA and Liposomes. The chemical characterization was carried out by determination of particle size, zeta potential, stability and encapsulation rates. Biological activity was tested in a panel of tumor cell lines by the MTT and SRB assays, and considering the biological activity of the drug-free compounds compared to nanosystems, the HCT 116 cell line was chosen to determine the mechanisms of action of these compounds. Tests of cell proliferation, membrane integrity, cell cycle, mitochondrial transmembrane potential, mechanism of cell death and phosphorylation of H2Ax were determined by flow cytometry. The Comet assay was performed to assess DNA damage. Staining of Panotico and Giensa were used to determine the morphological changes and formation of micronuclei, respectively. In silico assays for the determination of ADME/Tox (FAFDrug3) and targeting properties (Pharmmapper) were used for drug-biological predictions. The results showed that liposome encapsulation method was the most suitable for both Tambjamines, allowing the formation of stable nanosystems with high encapsulation rate (> 90%). Tambjamines I and J showed cytotoxic effects against all tested cell lines. They appear to induce cell death by apoptosis, with cell cycle arrest, mitochondrial depolarization, presence of DNA damage and formation of micronuclei in a concentration and time dependent manner, besides promoting intracellular pH modulation. The results with the encapsulated Tambjaminas showed these nanosystems compared to the free drug have a longer effect, denoting that the compounds have a great pharmacology potential.